1992
DOI: 10.1288/00005537-199208000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile nasopharyngeal angiofibroma contain an angiogenic growth factor: Basic FGF

Abstract: The presence of an angiogenic protein basic fibroblast growth factor (FGF) was established in juvenile nasopharyngeal angiofibroma (JNF). Extracts of these tumors have the capacity to stimulate endothelial cell proliferation. This activity is indistinguishable from basic FGF. The biological activity contained in the extracts binds to heparin-Sepharose columns and is eluted with a characteristic 2 mol sodium chloride. The exact fraction of the biological activity corresponds to the location where an immunoreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 19 publications
1
37
0
3
Order By: Relevance
“…Another study identified that GSTM1 (null genotype) is linked to the development of JNA [69]. SYK protein kinase (tyrosine kinase) is differentially expression in low and high stage JNA, suggesting a possible molecular treatment target, along with angiogenic protein basic fibroblast growth factor [70,71].…”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…Another study identified that GSTM1 (null genotype) is linked to the development of JNA [69]. SYK protein kinase (tyrosine kinase) is differentially expression in low and high stage JNA, suggesting a possible molecular treatment target, along with angiogenic protein basic fibroblast growth factor [70,71].…”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…Therefore, vascular endothelial growth factor (VEGF), nerve growth factor (NGF), insulin-like growth factor (IGF), fibroblast growth factor (FGF), platelet-derived growth factor (PDGF), and transforming growth factor (TGF) were assessed in many studies [2,5,6,10,12,[14][15][16]23,[25][26][27]. The levels of TGF-β1 [10,25,27,29], basic fibroblast growth factor (bFGF) [6,15,25,26], NGF (2), and VEGF [5,6,10,12,14,16,23,25] were found to be elevated in JNA. The most notable of which are TGF-β1 and VEGF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Porém, há indícios de que o comportamento tumoral varie com alterações dos níveis séricos hormonais. Schiff 34 , em sua tese sobre a patogênese do angiofibroma, descreveu em detalhes a presença de fibroblastos imaturos e células endoteliais, típicas do tumor e ressaltou que o quadro é revertido drasticamente pela ação estrogênica, que causa maturação histológica do tecido conjuntivo e das células endoteliais. Porém, Schiff não identificou a potencial origem do tumor.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Se de um lado a presença de receptores androgênicos é considerada um fato confirmado 12 , diferentes trabalhos da literatura acusam a ausência de receptores estrogênicos 9,35,36 , sugerindo uma ação indireta desse hormônio. Schiff 34 sugeriu um duplo mecanismo de ação dos estrógenos: redução da permeabilidade do tecido conjuntivo, reduzindo o número de vasos; e redução da produção de andrógenos por feedback negativo. Os achados desses autores apontam para a possibilidade de utilização de antiandrogênicos puros (flutamida, ciproterona) como uma alternativa aos tratamentos radioterápico e quimioterápico.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified